Identification of BRCA- and CHEK2-related breast cancer and ovarian cancer in women in outpatient oncology clinical practice (Russian Medical and Social Journal, 2019)
Introduction. Currently breast cancer is considered a heterogeneous disease and spectrum of several biological subtypes. Ovarian cancer is also characterized by a variety of molecular genetic alterations. Both diseases remain the leading specific causes of death in age group 40-49 and 50-59 for females.Objective: to evaluate the frequency of mutations in the genes BRCA1/2 and CHEK2 in patients with breast cancer and patients with ovarian cancer, as well as in women with benign neoplasms of the mammary glands, and to analyze their clinical and morphological correlations with the disease characteristics in the routine clinical practice of an outpatient oncologist.Patients and Methods: Seventy-six women were included in the present analysis. All of them were observed by the oncologist in Consultative and diagnostic center of Burdenko Main Military Clinical Hospital (Moscow) between January 2016 and May 2019, and were divided in three groups: patients with breast cancer (n=20), patients with ovarian cancer (n=17) and control group of women with benign neoplasms of the mammary glands (fibrocystic mastopathy in 29, breast fibroadenoma in 11), with no history of any oncological disease. One patient has metachronous malignant neoplasms of independent (primary) multiple sites: breast and ovarian cancer. All women were genotyped for pathogenic germline mutations 185delAG, 300T>C (Cyse61Gly), 2080delA, 3819delGTAAA, 3875delGTCT, 4153delA, 5382InsC in the gene BRCA1, mutation 6174delT in the gene BRCA2 and mutations IVS2+1G>A, I157T and IVS2+1G>A in the gene CHEK2 by polymerase chain reaction real-time using a set “OncoGenetics” (LLC «Research and Production Company DNA-Technology», Russia, registration certificate № 2010/08415).Results: Pathogenic germline BRCA1 mutations were identified in 4 (20%) patients with breast cancer, 3 (17,6%) patients with ovarian cancer and 1 (2,5%) women with breast fibroadenoma. Pathogenic germline CHEK2 mutations were identified in 3 (15%) patients with breast cancer, all cases were represented by the I157T mutation. In the control group carriers of BRCA1 or BRCA2 mutations (n=2) were associated with early onset development of breast fibroadenoma in the age before 30 years. The risk of BRCA or CHEK2 mutated genes was significant higher in patients with breast cancer (45%, HR 9.0, 95% CI: 2.14 - 37.8) compared with the control group of women with benign breast tumors (5%, p
Keywords: breast cancer; ovarian cancer; breast fibroadenoma; BRCA; CHEK2; age at diagnosis; grade tumor